Questioning strategy and academic reading performance: the case of low proficient students / Liyana Ahmad Afip - Ahmad Afip, Liyana (2011)
This research investigates whether questioning strategy could affect the reading performance of less proficient readers. The main objectives of the research were to 1) determine metacognitive strategies used by the less proficient readers in reading, 2) investigate students' perceptions of questioning strategy in reading, 3) investigate whether questioning strategy could affect students' reading performance and 4) investigate whether questioning strategy could affect students' reading performance by gender. The research employed a quasi-experimental design. A total of sixty low proficiency Form Six students were purposively selected and assigned into two groups namely the Experimental Group and the Control Group. The instruments used were questionnaire, a pre-test, a post-test, three reading lessons (using questioning strategy) and five open-ended questions for reflection session. Both groups had to answer a questionnaire, sit for a pre-test, participate in fliree reading lessons and sit for a post-test. Only the students in the Experimental Group had to participate in strategy training and reflection session. The findings revealed that non-proficient students were high reading strategy-users. The students in Experimental Group gave positive feedback regarding the use and effect of questioning strategy and the result from independent t-test and paired sample t-tests showed a significant difference, revealing the effectiveness of the strategy. It also had positively affected the reading performance of both male and female students in Experimental Group. These findings have direct implications on the teaching and learning English to the less proficient learners. It proves that strategies are trainable and there are avenues for teachers to help these students.